Impact of coronary chronic total occlusions on long-term mortality in patients undergoing coronary artery bypass grafting. (11th March 2014) - Fefer, Paul; Gannot, Sharon; Kochkina, Ksenya; Maor, Elad; Matetzky, Shlomi; Raanani, Ehud; Guetta, Victor; Segev, Amit
Abstract: OBJECTIVES: The presence of a coronary chronic total occlusion (CTO) is a common consideration in favour of surgical revascularization. However, studies have shown that not all patients undergoing coronary artery bypass grafting (CABG) have a bypass graft placed on the CTO vessel. The aim of this study was to determine the prevalence of CTO among patients referred for CABG and the significance of incomplete CTO revascularization in these patients. METHODS: The study included 405 consecutive patients undergoing CABG during a 2-year period. Clinical, echocardiographic and angiographic data were collected. Determination of whether or not a CTO was bypassed was made by correlating data from the surgical reports and preprocedural angiograms. The primary end point of this study was 5-year all-cause mortality. RESULTS: Two hundred and twenty-one CTOs were found in 174 patients: 132 patients (76) had 1 CTO; 37 (21) had 2 CTOs and 5 (3) had 3 CTOs. Of the 221 CTOs, 191 (86%) were bypassed. All left anterior descending (LAD) CTOs were grafted; however, 12 of left circumflex and 22% of right coronary artery CTOs did not receive bypass grafts. Incomplete CTO revascularization was associated with older age, more comorbidities, including stroke, renal impairment and lower ejection fraction. However, incomplete CTO revascularization was not associated with increased 5-year mortality. CONCLUSIONS: Coronary CTOs are a common finding in patients referred for bypass surgery. The presence of a CTO is not independently associated with an adverse long-term outcome. While most CTOs are successfully bypassed, failure to revascularize a non-LAD CTO is not associated with adverse long-term outcome.